2023
DOI: 10.23887/ijee.v7i1.58269
|View full text |Cite
|
Sign up to set email alerts
|

Website-Based Learning Media on Reading and Numeracy Content for Third Grade Elementary Schools

Abstract: Learning technology continues to improve along with the times. The role of technology currently has very rapid development in various fields. Many media can help improve the quality and quantity of learning, one of which is the application of website-based learning. This study aims to develop web-based learning media on reading and arithmetic content for third-grade elementary school students and test the feasibility of these learning media. This study used the R&D (Research and Development) development me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(50 reference statements)
0
2
0
1
Order By: Relevance
“…In general, the assessment results from material experts, media experts, and students showed that the media is in very good categories, indicating that the website is a highly effective learning medium. Other researchers have also developed website-based learning media to improve student learning outcomes, such as the website media developed to support learning in the fields of mathematics, physics, chemistry, language, and design (Arifin & Nugroho, 2023;Manggopa, Manoppo, Togas, Mewengkang, & Batmetan, 2019;Purba, Riris, & Muchtar, 2021;Rukun & Irfan, 2020;Suartini, Sukandar, Zadi, Fikadinda, & Maulana, 2022;Swandi et al, 2022). The cited studies suggest that website-based learning media is an effective tool for improving student learning outcomes.…”
Section: Figure 5 Tourist Destinations Displaymentioning
confidence: 99%
“…In general, the assessment results from material experts, media experts, and students showed that the media is in very good categories, indicating that the website is a highly effective learning medium. Other researchers have also developed website-based learning media to improve student learning outcomes, such as the website media developed to support learning in the fields of mathematics, physics, chemistry, language, and design (Arifin & Nugroho, 2023;Manggopa, Manoppo, Togas, Mewengkang, & Batmetan, 2019;Purba, Riris, & Muchtar, 2021;Rukun & Irfan, 2020;Suartini, Sukandar, Zadi, Fikadinda, & Maulana, 2022;Swandi et al, 2022). The cited studies suggest that website-based learning media is an effective tool for improving student learning outcomes.…”
Section: Figure 5 Tourist Destinations Displaymentioning
confidence: 99%
“…Pendidikan mengharapkan seseorang mampu mengembangkan potensi serta kemampuan secara maksimal sehingga dapat bersaing di era ini. Pendidikan biasanya dapat diperoleh melalui lembaga non formal ataupun formal yang salah satu lembaga formal awal yaitu sekolah dasar (Kristiyanto & Rahayu, 2020;Subali et al, 2019). Dalam menyelenggarakan pembelajaran di sekolah dasar harus melibatkan guru sebagai tenaga pendidik dan siswa sebagai peserta didik yang dapat diwujudkan dengan interaksi belajar.…”
Section: Pendahuluanunclassified
“…The comic medium has become one of the most popular forms of artistic expression in the world. With the use of strong images and narration, comics are able to describe stories that are interesting and touch readers (Kristiyanto & Rahayu, 2020). Comic media can be used to increase individual understanding (Febriyanti & Mustadi, 2020).…”
Section: Introductionmentioning
confidence: 99%